2014
DOI: 10.1167/iovs.13-13714
|View full text |Cite
|
Sign up to set email alerts
|

Mild Decentration Measured by a Scheimpflug Camera and Its Impact on Visual Quality Following SMILE in the Early Learning Curve

Abstract: This study suggests that, although mild decentration occurred in the early learning curve, good visual outcomes were achieved after the SMILE surgery. Special efforts to minimize induced vertical coma are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 21 publications
5
78
1
Order By: Relevance
“…28 In 100 eyes of 55 patients treated with SMILE, the mean total decentered distance from the corneal vertex was 0.17 6 0.09 mm (range, 0.02-0.49 mm) in an anterior elevation corneal topography map from the Scheimpflug Camera, and all eyes were within 0.50 mm of the corneal vertex. 12 Although the mean total decentration values from our study were slightly larger than those reported from other studies, techniques for calculating decentration varied. A direct comparison among the studies without considering centration analysis method should be performed with caution.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…28 In 100 eyes of 55 patients treated with SMILE, the mean total decentered distance from the corneal vertex was 0.17 6 0.09 mm (range, 0.02-0.49 mm) in an anterior elevation corneal topography map from the Scheimpflug Camera, and all eyes were within 0.50 mm of the corneal vertex. 12 Although the mean total decentration values from our study were slightly larger than those reported from other studies, techniques for calculating decentration varied. A direct comparison among the studies without considering centration analysis method should be performed with caution.…”
Section: Discussioncontrasting
confidence: 72%
“…26 On the other hand, one recent study evaluating the centration following the SMILE procedure found no statistically significant difference in induced ocular aberrations, rather than purely corneal aberrations, when comparing eyes with decentered distances greater than 0.30 mm to those within 0.30 mm. 12 Although the present study had several limitations, including its retrospective design, it is the first study to investigate lenticule decentration following the SMILE procedure on the tangential topography difference map of the Keratron Scout. On the basis of the current results, we concluded that minimal decentration in myopic SMILE is related to smaller induction of total HOAs, coma, vertical coma, horizontal coma, and spherical aberration.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The horizontal decentration was positively correlated with the quantity of induced horizontal trefoil; obversely, the vertical decentration did not result in HOA elevation. 57 …”
Section: Higher-order Aberrationsmentioning
confidence: 99%